Dissecting the Molecular Interactions between Wheat and the Fungal Pathogen Zymoseptoria tritici - Kettles, Graeme J.; Kanyuka, Kostya (Frontiers in Plant Science, 2016)
The Dothideomycete fungus Zymoseptoria tritici (previously known as Mycosphaerella graminicola and Septoria tritici) is the causative agent of Septoria tritici leaf blotch (STB) disease of wheat (Triticum aestivum L.). In Europe, STB is the most economically damaging disease of wheat, with an estimated ~€1 billion per year in fungicide expenditure directed towards its control. Here, an overview of our current understanding of the molecular events that occur during Z. tritici infection of wheat leaves is presented. On the host side, this includes the contribution of (1) the pathogen-associated molecular pattern-triggered immunity (PTI) layer of the plant defence, and (2) major Stb resistance loci to Z. tritici resistance. On the pathogen side of the interaction, we consolidate evidence from recent bioinformatic, transcriptomic and proteomic studies that begin to explain the contribution of Z. tritici effector proteins to the biphasic lifestyle of the fungus. This includes the discovery of chitin-binding proteins in the Z. tritici secretome, which contribute to evasion of immune surveillance by this pathogen, and the possible existence of ‘necrotrophic’ effectors from Z. tritici, which may actively stimulate host recognition in a manner similar to related necrotrophic fungal pathogens. We finish by speculating on how some of these recent fundamental discoveries might be harnessed to help improve resistance to STB in the world’s second largest food crop.